A educação para a cidadania digital na escola: análise multidimensional da atuação dos professores enquanto mediadores da cultura digital nos processos de ensino e de aprendizagem - Costa, Daniela (2019)
Technologies are not just technical tools, they are increasingly understood as languages through which individuals understand, construct, and appropriate the world. The practices arising from these exchange roles among technologies, media and individuals are called digital culture. Digital citizenship education is a further study of the relationship between education and digital culture and emphasizes the relevance of education about the media and technologies, understanding them as an object of debate and reflection. It is based on the assumption that individuals can take better advantage of the opportunities of media and technologies usage when they are more prepared to understand them critically. Digital citizenship education draws on participatory culture to enhance engagement as a form of expression of ideas, rights defense movements and involvement in political agendas. It also uses reflexive approaches of the digital literacy and studies on the interaction of children with technologies to enhance the role of critical reading of these resources as a form of conscious participation. Digital citizenship education also highlights the various types of inequalities that make such opportunities offered in different ways for certain groups. In this context, teachers play an extremely relevant role as mediators and agents engaged in the critical education of their students. However, it is necessary to reflect about teachers’ capabilities for this role. This includes another evaluation related to inequalities in opportunities for participation in digital culture and how they could impact teachers. In this sense, the aim of this thesis is to analyze the conditions, opportunities and capacities of the teachers acting as mediators of the participation of their students in the digital culture, in the scope of digital citizenship education. It is a multidimensional analysis, which considers not only the access and use of the technologies by teachers, but also the professional conditions, the structural characteristics of the schools where they work and the possible deprivation of their freedom of agency in these environments. In the development of the analysis, the Alkire-Foster method was applied to the microdata referring to the schools from the School Census 2017 (INEP, 2018), as well as to the microdata about teachers, based on the data collection carried out in the scope of the Survey on the use of information and communication technologies in Brazilian schools - ICT in Education 2017 (NIC.BR, 2018). It is expected that this analysis can contribute to the elaboration of more effective educational policies according to the social, cultural and economic contexts of the teachers and, consequently, of the students